Psychoanalytic Study of an Artist’s Mind in Mahesh Dattani’s Play Tara - Soomro, Samra (Journal of Research in Humanities, 2023)
This research focuses on the psychoanalytic study of an artist’s mind in Mahesh Dattani’s play Tara. Dan’s guilt is the cause of his failure as an artist. His misdirected assumption that his sister Tara lost one leg because of him makes him an escapist thus resulting in the phase of “incubation,” which in turn has a negative effect on the stages of “illumination” and “verification” that follow it in the creative model proposed by Wallas and Smith consulted form the article entitled “Creativity.” Due to his ensnaring guilt Dan does not realize that in the process he reconstructs himself as an object also, thus making it his tragedy as well. The analysis argued from the perspective of poststructuralist concepts discussed by Catherine Belsey in Critical Practice reveals that Dan is unable to justify his position as the “grammatical subject” as a result of the conflict initiated by his “subject-position” of a brother. The emphasis is to argue that Dan’s authority over the “subject of enonce” is possible only when he resolves his conflicts within the “subject of enunciation.”